First record of the occurrence and abundance of phorids (Diptera: Phoridae) associated with leaf-cutting ants of the genus Atta (Hymenoptera: Formicidae) in the municipality of Cruz das Almas-BA - Souza, T. D. [UNESP]; Pereira, R. C. (Universidade Estadual de Feira de Santana, 2020)
Leaf-cutting ants of the genus Atta are considered one of the main forest and agricultural pests. Currently, chemical control using granulated baits is considered the most efficient, however, with the inadequate adoption of management it can harm non-target organisms and the agro-ecosystem. Phorid parasitoids have been studied so that they can be used as an alternative management strategy for leaf-cutting ants. The use of phorids as part of the management strategy in biological control, despite being still very incipient, may in the future become a safer alternative for the control of leaf-cutting ants. Thus, the objective was to report the occurrence of parasitoids of the family Phoridae associated with leaf-cutting ants of the genus Atta in the municipality of Cruz das Almas. During the months of April to July, three environments were studied, being: pasture area, eucalyptus plantation and a fragment of Atlantic Forest. In each of these environments, three colonies of two species of ants Atta sexdens sexdens and Atta laevigata were selected. Each collection consisted of six hours of observation, divided into eight periods of 45 minutes. Observations were made on the trails and scouts consecutively, always starting with the scout. A total of 112 phorids belonging to two genera were collected, being 64 to genus Eibesfeldtphora and 48 the genus Myrmosicarius.
Keywords: Eibesfeldtphora; Myrmosicarius; Parasitoid; Phoridae